A Simplified Model to Assess the Influence of the Configuration of Commercial Aircraft on Boarding and Deboarding. (9th February 2021) - de Oliveira, Diogo B. P.; Coelho, Jonathan N.; Moraes, Alison de O.
Abstract : This paper presents an evaluation of the influence of aircraft configuration on the boarding and deboarding times using a simplified model and computer simulation. Boarding and deboarding times are important to airlines since both procedures are part of the critical path of the turnaround time (TAT) of aircraft in airports. During the TAT, a series of activities are performed in the aircraft in order to prepare it for the next flight. A reduction in boarding and deboarding times may represent a reduction in TAT for airlines. For the comparisons, three aircraft configurations are used: single aisle 3 × 3 ("six abreast"), single aisle 3 × 2 ("five abreast"), and single aisle 2 × 2 ("four abreast"), all with the same number of passengers. For the boarding analyses, two boarding procedures are used: random and random outside-in. The 2 × 2 aircraft interior configuration holds the shortest boarding times; deboarding times are similar for the three configurations. Also, a sensitivity analysis is carried out, and the results show that the higher the aircraft occupancy and the number of passengers with carry-on baggage, the higher are boarding and deboarding times, with the 2 × 2 having the lowest times in comparison with the other two configurations.